A Problem-Based Learning (PBL) and Teaching Model using a Cloud-Based Constructivist Learning Environment to Enhance Thai Undergraduate Creative Thinking and Digital Media Skills - Srikan, Parawee; Pimdee, Paitoon; Leekitchwatana, Punnee; Narabin, Akan (My University, 2021)
The objective of this research was to develop a Problem-Based Learning (PBL) Model which used a cloud-based constructivist learning environment to enhance Thai undergraduate creative thinking and digital media skills. Initially using a mixed-methods approach, a five-step model was conceptualized. Thereafter, a panel of five academic experts gave input into the model’s design from which the model was expanded to include six related learning environments. The instrument used in the research was a problem-based assessment form. Data collection was carried out utilizing group chats and analyzed using descriptive statistics including the mean and standard deviation. The results of the study revealed that the initial model contained five steps including (1) problem identification, (2) problem analysis, (3) research, (4) presentations, and (5) summary and evaluation, which is integrated into the model’s additional six learning environment elements. These six learning environments were (1) problem-based, (2) resources, (3) cognitive tools, (4) collaboration, (5) scaffolding, and finally, (6) coaching. When applying the proposed model and related environments, there was a consensus from the experts that the model had excellent suitability and can be used as a model for teaching and learning at the bachelor’s degree level.
Keywords: computational thinking; critical thinking; internet; Thailand